The New Developments in International Investment Law: A need for Multilateral Investment Treaty? - Forere, Malebakeng A (Potchefstroom Electronic Law Journal, 2018)
This work contributes to the global discussion on the desirability of the multilateral investment treaty to ensure coherence in the way foreign investment is protected across the globe. The paper argues that whereas the international community is not ready yet to adopt multilateral rules on investment liberalisation, the time is ripe for multilateral rules on the standards of protection backed up by a multilateral court with a two-tier system. Most importantly, this contribution provides a template for the content of the standards of protection, having observed the new approaches to the traditional standards of protection typically enshrined in the bilateral investment treaties.